Polaronic correlations from optimized ancilla wave functions for the Fermi–Hubbard model - Tobias Müller; Ronny Thomale; Subir Sachdev; Yasir Iqbal (Proceedings of the National Academy of Sciences, 2025)
We employ a family of ancilla qubit variational wave functions [Y.-H. Zhang and S. Sachdev, Phys. Rev. Res. 2 , 023172 (2020)] to describe the polaronic correlations in the pseudogap metal phase of a hole-doped 2D Fermi–Hubbard model. Comparison to ultracold atom quantum simulator data [J. Koepsell et al ., Science 374 , 82 (2021)] reveals both qualitative and quantitative agreement with the numerical analysis from half-filling up to 80% hole-doping, capturing the crossover from the polaronic regime to the Fermi liquid observed around 40% doping.